واقع المحاسبة العمومية في ظل التوجه نحو المعايير الدولية للقطاع العام IPSAS - محمد رشاد, عميار; رضا, زين; يوسف, زيد (جامعة الوادي - University of Eloued, 2023)
"تهدف هذه الدراسة إلى تشخيص واقع المحاسبة العمومية في الجزائر، وإبراز أهمية تبني معايير المحاسبة الدولية في القطاع العام، وكذلك التعرف على الإصلاحات التي باشرتها الجزائر في إطار عصرنة نظام المحاسبة العمومية، والتي تهدف إلى مواكبة الممارسات المحاسبية الدولية، وكذا الوقوف على مشروع الإصلاح الميزانياتي خاصة في ما يتعلق بالإطار القانوني والتشريعي والتنظيمي، وأثر ذلك على عقلنة ترشيد الإنفاق العمومي. أفضت نتائج الدراسة إلى على أن تطوير وعصرنة نظامي المحاسبة العمومية والميزانية العمومية تعتبر وسيلة للاستخدام الأمثل للمال العام ، والعمل على محاربة الفساد المالي والإداري مما يسهم في ترشيد وعقلنة الإنفاق العمومي للدولة ، كما ان معايير المحاسبة الدولية للقطاع العام تسعى إلى تقريب المحاسبة العمومية بالمحاسبة المالية ، حيث إن مشروع عصرنة النظام المحاسبي و الموازناتي العمومي المطبق حديثا من طرف وزارة المالية بالجزائر جاء متوافقا لحد بعيد مع متطلبات تبني معايير المحاسبة الدولية للقطاع العام ، كما إن إعتماد أسلوب ميزانية البرامج والأداء، يسمح بتوفير المزيد من الضمانات لترشيد انفاق الأموال العمومية في الجزائر. ""This study aims to diagnose the reality of public accounting in Algeria، And highlight the importance of adopting international accounting standards in the public sector، As well as identifying the reforms undertaken by Algeria within the framework of modernizing the public accounting system، Which aims to keep pace with international accounting practices، As well as standing on the budgetary reform project, especially with regard to the legal, legislative and regulatory framework، And the impact of this on the rationalization of public spending . The results of the study led to the fact that the development and modernization of the public accounting systems and the balance sheet is considered a means for the optimal use of public money, and work to combat financial and administrative corruption, which contributes to the rationalization and rationalization of public spending for the state, and the international accounting standards for the public sector seek to approximate public accounting with financial accounting, As the project of modernizing the accounting system and public budgets recently applied by the Ministry of Finance in Algeria came to a large extent compatible with the requirements of adopting international accounting standards for the public sector, and the adoption of the program and performance budget method allows for the provision of more guarantees to rationalize the expenditure of public funds in Algeria. "
Keywords: المحاسبة العمومية، معايير المحاسبة الدولية للقطاع العام، الإصلاح الميزانياتي; public accounting، International Public Sector Accounting Standards، Budget reform .